Factors hindering the development of small-scale municipal hydropower: a case study of the Black River project in Springfield, Vermont - Peters, E.; Berger, G.; Amlin, J.; Meadows, D. (Dartmouth Coll., Hanover, NH (USA). Thayer School of Engineering, 1979)
There are many good reasons to use New England's small-scale hydropower resources to generate electricity. But current production capacity in the three northern states is only 1300 MW, just 35% of the 3710 MW estimated to be available to the states. Though the benefits of properly designed projects seem substantial, many factors combine to hinder their development. The Black River project in Springfield, Vermont, exemplifies the problem. Even after the two has invested over five years and $1 million in its effort to develop 30 MW of capacity, it still has not received either federal or state approval to proceed with construction. The first 4 years of the Springfield experience are described and factors that have greatly increased the cost and planning time for the project are identified. The purpose is to identify changes that could facilitate efforts to develop small-scale hydropower at other acceptable sites. On the basis of this experience it is recommended that: after issuance of a FERC permit, a preliminary determination of the project's impacts should be made by FERC officials; if environmental impacts are solely local or limited, environmental analysis/determination should be placed in the hands of the state; short-form licensing should be used for all run-of-river hydro projects that utilize and do not significantly modify existing water impoundment areas and do not significantly alter downstream flow patterns; and a hydro ombudsman with power at the state level should be established to facilitate governmental inter-agency coordination and project-related information transfer: one-stop licensing. (LCL)